2019
DOI: 10.3390/su11061542
|View full text |Cite
|
Sign up to set email alerts
|

Employability of Disabled Graduates: Resources for a Sustainable Employment

Abstract: In the frame of the psychology of sustainability, this research aims at exploring how the related concepts of risk factors, protective factors, and resilience might inform our understanding of the postgraduate outcomes of disabled youth. The number of disabled students is growing steadily, nevertheless, relatively little is known about the employment experiences and skill development of disabled youth. Following the positive primary preventive approach, this explorative research investigates the role of resili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 75 publications
2
18
0
Order By: Relevance
“…With the results of this research we confirmed that for a sustainable organizational development is need to promote a sustainable employment [62] but also a sustainable, innovative and easy to use tool for employability measurement because in the most of the organizations the employees must match the corporate culture [27].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…With the results of this research we confirmed that for a sustainable organizational development is need to promote a sustainable employment [62] but also a sustainable, innovative and easy to use tool for employability measurement because in the most of the organizations the employees must match the corporate culture [27].…”
Section: Discussionsupporting
confidence: 70%
“…Our results also demonstrate that regarding the Eurostat describers for quality of employment and skill-related statistics arenot the risk factors that hinders perceived employability for employers and infirmed the international results [62].…”
Section: Discussionsupporting
confidence: 64%
“…A systematic review carried out by some authors [17] [18] shows that across 13 studies, a total of 7 unique predictors of post-secondary competitive employment were identified such as paid employment while attending high school, Individual Educational Plan (IEP) goals or vocational skills [19], as shown in Figure 1. These predictors, alongside other factors, were found to help students with intellectual or developmental disabilities to secure a job after post-secondary education.…”
Section: A Challenges Of Employmentmentioning
confidence: 99%
“…However, the employment rate in the case of people with disabilities is considerably lower than of non-disabled people. The employment gap between people with disabilities and those without is determined by demographic and economic factors, as well as national welfare policies, but with no definitive empirical evidence on their relative strength [17].…”
Section: Introductionmentioning
confidence: 99%